Perception of Women's Exposure to Birth in the Forest – A Cross-Sectional Study on Yei Tribe, Merauke Regency, Indonesia - Indah, Fenita Purnama Sari; Andriati, Riris; Rohmawati, Ika; Kartikasari, Rina; Rachmaniah, Dini; Andiyan, Andiyan (Folia Medica Indonesiana, 2022)
Highlights: • The maternal mortality for women's exposed birth in the forest on Tribe Kampung Poo, Merauke Regency is higher. • Mother's knowledge perceptions of women's exposure to birth in the forest were more dominant than community leader's roles, husband or family roles and respondent characteristics. Abstract: In one of the districts in Papua, namely the Merauke Regency, the maternal mortality number in 2016 reached 17 cases, 13 cases in 2017, 6 cases in 2018, 9 cases in 2019, and 7 cases in 2020. Data in 2020 showed that 4,163 of the 5,377 deliveries by health workers assistance in Merauke Regency had not been fully achieved. There were 4,098 deliveries carried out in health care facilities. This study analyzed determinant factors on perceptions of the exile women giving birth in the forest from women of Yei Tribe, Poo Village, Merauke Regency, Indonesia. This study used analytic design methods with a cross-sectional approach. The sampling was non-probability with a total sample method of 57 mothers with toddlers. Univariate analysis was used to describe the characteristics of each research variable, including respondent characteristics, mother's knowledge, the role of community leaders, and the role of husband or family, while the dependent variable was the perception of women giving birth in the forest. This study found that there was a correlation between education (p-value 0.000; OR=13.33), knowledge (p-value 0.000; OR=133.00), the community leaders' role (p-value 0.009; OR=5.00), and husband's role (p-value 0.000; OR=28.00) with perceptions of the exile women giving birth in the forest at women of Yei Tribe, Poo Village, Merauke Regency, Indonesia. Therefore, knowledge is dominant in the perceptions of exiled women giving birth in the forest.